The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.7150/thno.60437
|View full text |Cite
|
Sign up to set email alerts
|

Co-delivery of autophagy inhibitor and gemcitabine using a pH-activatable core-shell nanobomb inhibits pancreatic cancer progression and metastasis

Abstract: Background: Metastasis is one of the main reasons for the high mortality associated with pancreatic ductal adenocarcinoma (PDAC), and autophagy regulates the metastatic migration of tumor cells, their invasion of tissues, and their formation of focal adhesions. Inhibiting autophagy may suppress tumor growth and metastasis, but the abundant extracellular matrix hinders the deep penetration of therapeutic agents. Methods: To enhance the penetration of drugs that can inhibit met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…The stroma in some PDAC tumors can account for up to 90% of the tumor mass [ 244 ]. This has led to the development of nanoparticles bound to chemotherapeutics or core capsules that can deliver a nano-bomb of compounds to aid the delivery [ 245 , 246 ]. This protective stroma is fundamental to PDAC survival, aggressive nature and chemotherapeutic resistance.…”
Section: Pancreatic Tumor Microenvironment and Autophagymentioning
confidence: 99%
See 1 more Smart Citation
“…The stroma in some PDAC tumors can account for up to 90% of the tumor mass [ 244 ]. This has led to the development of nanoparticles bound to chemotherapeutics or core capsules that can deliver a nano-bomb of compounds to aid the delivery [ 245 , 246 ]. This protective stroma is fundamental to PDAC survival, aggressive nature and chemotherapeutic resistance.…”
Section: Pancreatic Tumor Microenvironment and Autophagymentioning
confidence: 99%
“…PDAC chemotherapy is largely ineffective due to the protective stroma and can be further suppressed if tumor cells are actively opposing apoptosis [ 118 , 295 ]. This interaction could also explain why combination therapy involving autophagy inhibition is highly synergistic [ 179 , 246 , 291 ].…”
Section: Autophagy In Pancreatic Cancer Progressionmentioning
confidence: 99%
“…Therefore, it is necessary to design versatile and biocompatible nanoplatforms for realizing specific delivery and responsible release of ultrasmall nanoparticles. In addition, these nanoplatforms must possess the ability to act as large-sized nanoparticles for high accumulation while behaving as small-sized nanoparticles for deep penetration 11 - 15 . Nanoparticles ranging from 50 to 100 nm in diameter exhibit high tumor accumulation because of quick renal clearance available to the smaller nanoparticles and difficulty in transportation in interendothelial gaps of tumor vasculature in case of the larger ones.…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles ranging from 50 to 100 nm in diameter exhibit high tumor accumulation because of quick renal clearance available to the smaller nanoparticles and difficulty in transportation in interendothelial gaps of tumor vasculature in case of the larger ones. For instance, Shen group reported that the micelles of 100 nm, composed of amphiphilic block copolymers of 7-ethyl-10-hydroxylcamptothecin (SN38) prodrug, could accumulate in tumors best with sizes ranging from 35 and 150 nm 15 . Moreover, in case of nanoparticles smaller than 20 nm, penetration can be deeper than the larger ones owing to the dense extracellular matrix of tumor 11 .…”
Section: Introductionmentioning
confidence: 99%
“…With the development of molecular biology and the deep understanding of the tumor immune microenvironments, BMCT has once again aroused the interest of researchers as a promising approach for cancer therapy. Hypoxia, vascular abnormalities, low pH, and necrotic areas are common features of solid tumors (Guo et al, 2020;Chen et al, 2021b;Kang et al, 2022), and they are the main barriers for traditional therapies. However, they provide favorable conditions for the targeting, colonization, and replication of some obligate or facultative anaerobes.…”
Section: Introductionmentioning
confidence: 99%